Beyond Medical "Missions" to Impact-Driven Short-Term Experiences in Global Health (STEGHs): Ethical Principles to Optimize Community Benefit and Learner Experience. (May 2016) - Melby, Melissa K.; Loh, Lawrence C.; Evert, Jessica; Prater, Christopher; Lin, Henry; Khan, Omar A.
Abstract : Increasing demand for global health education in medical training has driven the growth of educational programs predicated on a model of short-term medical service abroad. Almost two-thirds of matriculating medical students expect to participate in a global health experience during medical school, continuing into residency and early careers. Despite positive intent, such short-term experiences in global health (STEGHs) may exacerbate global health inequities and even cause harm. Growing out of the "medical missions" tradition, contemporary participation continues to evolve. Ethical concerns and other disciplinary approaches, such as public health and anthropology, can be incorpo rated to increase effectiveness and sustainability, and to shift the culture of STEGHs from focusing on trainees and their home institutions to also considering benefits in host communities and nurtur ing partnerships. The authors propose four core principles to guide ethical development of educational STEGHs: (1) skills building in cross-cultural effective ness and cultural humility, (2) bidirectional participatory relationships, (3) local capacity building, and (4) long-term sustainability. Application of these principles highlights the need for assessment of STEGHs: data collection that allows transparent compar isons, standards of quality, bidirectionality of agreements, defined curricula, and ethics that meet both host and sending countries' standards and needs. To capture the enormous potential of STEGHs, a paradigm shift in the culture of STEGHs is needed to ensure that these experiences balance training level, personal competencies, medical and cross-cultural ethics, and educational objectives to minimize harm and maximize benefits for all involved.